THE ROLE OF ASSESSMENT IN STUDENT DEVELOPMENT - Rashidova Ruxshonaxon Rustamjon qizi (Western European Studies, 2024)
This article suggests that Assessment plays a critical role in student development, providing insight into individual learning progress and understanding. This helps teachers identify students' strengths and weaknesses and allows them to tailor instruction to meet each student's unique needs. Assessment also promotes self-reflection and goal-setting, encouraging a growth mindset and boosting motivation. By providing feedback and measuring student achievement, assessment serves as a tool for continuous improvement and accountability in the learning process
Keywords: methods; instruments; educational assessment; knowledge